2022
DOI: 10.1039/d2ra03673h
|View full text |Cite
|
Sign up to set email alerts
|

Effective regulation of the electronic properties of a biphenylene network by hydrogenation and halogenation

Abstract: The electronic properties of a biphenylene network can be effectively regulated in the range of 0.00–4.86 eV by hydrogenation and halogenation, and some of the obtained functionalized biphenylene networks have the potential to photolyse water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
(49 reference statements)
3
9
0
Order By: Relevance
“…In g configuration, all C-H bonds along the z-axis direction or the opposite direction of z-axis, which results in the structure of g configuration is more symmetric than other configuration and increase the stability. The above results agrees with the results of Xie et al 15 Their results indicate that the way hydrogen atoms are added to g configuration produces the most stable hydrogenated biphenylene, and the most stable binding energy for hydrogenated biphenylene in their calculations was 0.43 eV in magnitude, which is very close to ours. Liao et al 42 also found the g configuration through structure search software and provided evidence that the g configuration is a kind of very stable configuration among hundreds of candidates.…”
Section: Structuresupporting
confidence: 92%
See 2 more Smart Citations
“…In g configuration, all C-H bonds along the z-axis direction or the opposite direction of z-axis, which results in the structure of g configuration is more symmetric than other configuration and increase the stability. The above results agrees with the results of Xie et al 15 Their results indicate that the way hydrogen atoms are added to g configuration produces the most stable hydrogenated biphenylene, and the most stable binding energy for hydrogenated biphenylene in their calculations was 0.43 eV in magnitude, which is very close to ours. Liao et al 42 also found the g configuration through structure search software and provided evidence that the g configuration is a kind of very stable configuration among hundreds of candidates.…”
Section: Structuresupporting
confidence: 92%
“…14 This biphenylene network is the first experimentally synthesized planar graphene allotrope composed entirely of sp 2 hybridized carbon atoms. 15 Due to the superior properties of sp 2 -hybridized carbon materials, this experimentally synthesized biphenylene network structure is of great interest, and many researchers have carried out research on it over the past years. [16][17][18][19] The research of Liu 17 found that there is sufficient mechanical stability and no imaginary frequency in the phonon spectrum for biphenylene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon-only structures with different ring topologies may exist and this can be verified experimentally, for example, a biphenylene network composed of four-, six- and eight-membered carbon rings [ 35 , 36 ]. Recently, complex carbon nanostructures have been found in diamond [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al successfully synthesised the ultra-flat BPN with regularly spaced four, six, and eight-membered rings of sp 2 carbon atoms via a bottom-up approach [21]. Yunhao et al and Seunghan et al individually reported the modulation of the electronic properties of BPN by varying the concentration of hydrogen and halogens at different sites [22,23]. Bafekry et al reported the electronic and dielectric properties of BPN using the first principle calculation [24].…”
Section: Introductionmentioning
confidence: 99%